Erwerbstheoretische und glottodidaktische Aspekte des frühen Zweitspracherwerbs. Sprachentwicklung der Kinder im natürlichen und schulischen Kontext - Sopata, Aldona (Wydawnictwo Naukowe UAM, 2009)
In the present book, the dynamics of child second language development in various contexts is investigated. The main goal of the work is to shed some light on the mechanisms of early second language acquisition through a detailed analysis of the language development of children starting their second language acquisition both at different ages and in various contexts. The results of the empirical study are interpreted in the light of the main theories in the first and second language acquisition research, as well as in psycholinguistics. The pedagogical implications of this research deal with effective teaching and learning processes in the early foreign language education. The first part of the book is a critical analysis of the state of research in such fields as first and second language acquisition. The empirical findings are presented in the second part of the monograph. The study investigates the longitudinal data from children, who were exposed to their second language German in naturalistic setting. The variable of the age of onset is the main variable which differentiates them. The author investigates the acquisition of the same grammatical phenomena in the developmental sequence of children acquiring German in a school setting. The results of the empirical study show that both factors, the age of the onset of acquisition and the learning context, have a great impact on the course of acquisition. Starting second language acquisition around age three can lead to a process similar to the first language acquisition. The acquisition of the second language at a later age results in a type of acquisition in which both elements from the first and adult second language acquisition are present. The school context seems to be insufficient to create the environment for a developmental sequence characteristic to child second language acquisition in the naturalistic setting. The last part of the book contains a theoretical interpretation of the empirical findings from different perspectives, and the pedagogical implications for developing an optimal outline for foreign language teaching in early childhood.
Theoretical and pedagogical aspects of child second language acquisition. Children’s language development and pedagogical aspects of child second language acquisition. Children’s language development in naturalistic and school settings